Thymopoiesis in Pre- and Post-Hematopoietic Stem Cell Transplantation - Rocha, Luis Klaus A. da; Freschi de Barros, Samar; Bandeira, Francine; Bollini, Alexia; Testa, Lucia Helena de A.; Simione, Anderson João; Souza, Marina de O. e; Zanetti, Lilian P.; Oliveira, Leila Cibele S. de; Santos, Ana Claúdia F. dos; Souza, Mair Pedro de; Colturado, Vergílio Antônio R.; et al. (Frontiers in Immunology, 2018)
Hematopoietic stem cell transplantation (HSCT) is an important therapeutic option for some hematological diseases. However, patients who undergo HSCT present a state of immunodeficiency that causes significant mortality. Reconstitution of thymic function is needed to support the immune system. One way to measure thymic function is through T-cell receptor excision circle (TREC) quantification. TRECs are generated by T-cell receptor gene rearrangements during T-cell maturation in the thymus and represent a reliable marker for thymic output. In this study, we aimed to assess aging and malignant hematological diseases as two important factors that may influence the thymic output before HSCT. We observed that patients before the HSCT presented sjTREC lower than 606.55 copies/µg DNA (low values) compared with healthy individuals, with an odds ratio (OR) of 12.88 (95% confidence interval [CI]: 5.26-31.53; p < 0.001). Our results showed that older individuals (≥ 50 years old), healthy individuals and patients (n=165) had an OR of 10.07 (95% CI: 2.80-36.20) for low values of sjTREC copies compared with younger individuals (≤ 24 years old; p < 0.001). Multiple logistic regression analysis confirmed that both older age (≥ 50 years old) and prior treatment for malignant hematological diseases were two important and independent risk factors related to thymic function impairment (p < 0.001). Furthermore, the sjTREC median value for all ages was significantly lower than the sjTREC median for the subgroup of older healthy individuals (≥ 50 years old; p < 0.001). These data suggested that patients before HSCT and healthy individuals exhibited age-dependent thymic impairment and that prior treatment for hematological diseases may exacerbate aging-related deterioration of natural thymic function.